Integral mean δ-subharmonic functions and classes of almost regularly increasing - Tarasyuk , S. І. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Classes $Λ_δ$ of functions of finite $λ$-type $δ$-subharmonic in $\mathbb R^m$ are investigated. A membership criterion that defines when a function belongs to the class $Λ_δ$ expressed in terms of its integral q-means is established. Classes of entirely regular growth of functions that are $δ$-subharmonic in $\mathbb R^m$ are introduced and the behavior of these functions at infinity and the distribution of Riesz-associated measures are studied.